Management of neonatal upper limb trauma complicated by arterial injury: A case report - Man Duc Minh Phan; Ly Thi Thanh Nguyen; Tien Minh Nguyen; Phi Duong Nguyen (Trauma Case Reports)
This case report presents the clinical course and management of a 29-day-old female infant who presented with upper limb trauma secondary to entrapment beneath a sewing machine. Following admission, the patient exhibited clinical signs consistent with arterial injury and compartment syndrome, necessitating prompt diagnostic evaluation and surgical intervention. Despite challenges in arterial visualization via Doppler ultrasound, radiographic imaging confirmed displaced distal humerus fracture of the left upper limb, prompting further evaluation and surgical planning. Surgical decompression and stabilization were performed, followed by successful endovascular intervention utilizing digital subtraction angiography (DSA) to restore arterial perfusion. Subsequent development of compartment syndrome necessitated emergent fasciotomy, followed by wound care and skin grafting. Multidisciplinary rehabilitation facilitated optimal recovery, with the patient demonstrating improved motor function and sensory perception at six-month follow-up. This case underscores the importance of timely recognition, multidisciplinary collaboration, and prompt intervention in managing pediatric upper limb trauma complicated by arterial injury and compartment syndrome.